Behaviour of reinforced concrete columns strengthened by external prepacked concrete jacketing under uniaxial compression - Guo, Desheng. (2008)
Strengthening of reinforced concrete columns using reinforced concrete jacket has been widely practiced around the world. Although numerous structures have been repaired and upgraded in this manner during the last decade, limited experimental data are available on the behavior of jacketed columns, especially when the jacketing is introduced under loading or under some degree stress relief conditions. The purpose of the research project was to investigate the behavior of reinforced columns jacketed by high strength prepacked concrete.